2018
DOI: 10.1002/jpln.201700074
|View full text |Cite
|
Sign up to set email alerts
|

American beech leaf‐litter leachate chemistry: Effects of geography and phenophase

Abstract: The decomposition of broadleaved tree leaves can contribute a substantial amount of energy to forested watersheds via dissolved organic matter (DOM), nutrients, and biological activity. Less is known about how these inputs may vary within a single tree species that is known to have two genetically distinct and geographically separate populations, or how these inputs may change throughout autumn senescence and abscission. It is often implicitly assumed that intraspecific differences in leaf‐litter leachate chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…1b) is similar to HIX measured in extracts of organic soils (Zsolnay et al 1999) while the lower end of our range of measured HIX corresponds to autochthonous estuarine DOM (Huguet et al 2009) and corn vegetation leachate (Ohno 2002). The FI measured in our urban leachates and stormwater spans the extent of values measured in natural waters (e.g., McKnight et al 2001;Jaffé et al 2008;Hansen et al 2016) and is similar to FI measured in urban stream with similar percentages of impervious cover in their watersheds (Parr et al 2015), while observed values of BIX are low relative to most inland waters (e.g., Huguet et al 2009;Para et al 2010;Helms et al 2013;Dong et al 2014; Xu and Guo 2017) but comparable to measurements of BIX in leaf leachates (Yang et al 2015;Chen et al 2016;Hudson et al 2018).…”
Section: Fluorescence-based Measurements: Initial Valuessupporting
confidence: 78%
“…1b) is similar to HIX measured in extracts of organic soils (Zsolnay et al 1999) while the lower end of our range of measured HIX corresponds to autochthonous estuarine DOM (Huguet et al 2009) and corn vegetation leachate (Ohno 2002). The FI measured in our urban leachates and stormwater spans the extent of values measured in natural waters (e.g., McKnight et al 2001;Jaffé et al 2008;Hansen et al 2016) and is similar to FI measured in urban stream with similar percentages of impervious cover in their watersheds (Parr et al 2015), while observed values of BIX are low relative to most inland waters (e.g., Huguet et al 2009;Para et al 2010;Helms et al 2013;Dong et al 2014; Xu and Guo 2017) but comparable to measurements of BIX in leaf leachates (Yang et al 2015;Chen et al 2016;Hudson et al 2018).…”
Section: Fluorescence-based Measurements: Initial Valuessupporting
confidence: 78%
“…As we hypothesized, spring transition dates were more similar across data sources than autumn ones. This mismatch between PhenoCam GCC autumn transition dates and NDVI and EVI (low R 2 values and high biases) has been found in numerous other studies (e.g., Hufkens et al, 2012;Keenan et al, 2014a;Klosterman et al, 2014;Richardson et al, 2018b;Zhang et al, 2018). This is most likely due to physiological differences between the different metrics (i.e., GCC, NDVI, and EVI) that become more apparent in the autumn, with changes in color and canopy structure often occurring separately.…”
Section: Spring and Autumn Comparedmentioning
confidence: 70%
“…Based off of the similarity found here between GOES and Pheno-Cam at marking the start and middle of spring, the mismatch between MODIS and PhenoCam is likely largely due to the temporal resolution of the MODIS products. Hufkens et al (2012) also point out that the temporal resolution of MODIS products cannot be expected to precisely track rapid leaf emergence in the spring due to the longer temporal resolution. By averaging over a relatively long time period (compared to the length of spring green-up), such techniques likely prematurely inflate NDVI and EVI values, giving the false impression that green-up occurred earlier.…”
Section: Spring Transition Date Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of leaf phenology is ubiquitous across many processes and relationships in ecology, local and regional climates, and weatherranging from leaf-trait relationships, nutrients in leaf litter leachate, surface roughness, transpiration, leaf-spectra relationships, albedo and energy budgets, and annual primary productivity (Alekseychik et al, 2017;Hudson et al, 2018;McKown et al, 2013;Piao et al, 2019;Richardson et al, 2012;Schwartz et al, 2002;Xue et al, 1996;Zhu and Zeng, 2017).…”
Section: Introductionmentioning
confidence: 99%